Understanding stability and reactivity of transition metal single-atoms on graphene - Wesley Oliveira Morais; João Paulo Cerqueira Felix; Gabriel Reynald da Silva; Carlos Maciel de Oliveira Bastos; Alexandre C. Dias; Efracio Mamani Flores; Celso R. C. Rêgo; Vinícius da Silva Ramos de Sousa; Diego Guedes-Sobrinho; Maurício J. Piotrowski (Scientific Reports)
Abstract Recently, single-atom catalysts (SACs) based on transition metals (TMs) have been identified as highly active catalysts with excellent atomic efficiency, reduced consumption of expensive materials, well-defined active centers, and tunable activity and selectivity. Furthermore, when carbon-based supports (including graphene-derived materials) are employed in SACs, their unique structural and electronic properties, such as high electrical conductivity and mechanical strength, can be integrated. However, for this application, the primary objective is to maintain proper stability-reactivity balance, ensuring the system remains stable while preserving its high chemical activity. In this context, we explore the adsorption behavior of TM single atoms (Co, Ni, Rh, Pd, Ir, Pt) on pristine graphene (pGR), hexagonal boron nitride (hBN), and graphene with monovacancies (GRm) using DFT-PBE+D3 calculations. From the adsorption energy trends, we observe weak chemisorption on pGR and physisorption on hBN, with adsorption energies ranging from 0.5 eV (Co/hBN) to 1.80 eV (Rh/pGR). In contrast, the adsorption strength is significantly enhanced on GRm (strong chemisorption), with adsorption energies reaching up to 9.11 eV for Ir/GRm, attributed to the strong defect-induced reactivity and improved orbital overlap. Electronic structure analysis reveals that pGR retains its semimetallic nature, hBN remains an insulator, and GRm transitions to metallic behavior due to the strong interactions between TM-C. Bader charge analysis indicates significant charge transfer in GRm, consistent with its catalytic potential, while hybridization indices show substantial pd orbital mixing, favoring improved TM anchoring. Thus, our results identify GRm as the most promising substrate for SACs, pGR as a balanced platform for controlled reactivity, and hBN as a stable support for selective catalysis or dielectric applications. Finally, defect engineering is a powerful strategy for designing next-generation catalysts, ensuring the right balance between stability and reactivity.